Transitive and Intransitive Sentences in Savu Language - Olivia de Haviland Basoeki; Lusia Eni Puspandari; Rulli Saragi (Politeknik Negeri Padang, 2019)
Language is a communication tool that is seen as a channel for delivering information or messages to others. Language is expressed through sentences that composed of several words in order to form a certain meaning. To form a certain sentence which is apply in a language must follow its rules. For example, Indonesian has a main element that must exist in a sentence, namely predicate or verb. The verb forms become the basic of forming the various sentences, including in determining the types of transitive and intransitive sentences. Predicate or verb is one characteristic that determines whether the sentence is transitive or intransitive in language skills. This reason is one of the authors' interests in discussing more details about the transitive and intransitive sentences of Savu language, which is one of the local languages in the East Nusa Tenggara Province, with speakers of the Savu tribe. Transitive and intransitive sentences in Savu have the most flexible additional elements which can be accompanied by various kinds of objects and adverb. Transitive sentences have two core arguments that are broadly called actors and undergoers, as in the following sentence: (1) ana no era do due do; (2) ta ngedi ke no pidu bue moto; these two transitive sentences of Savu have two core arguments. The predicate on transitive sentences, namely: era 'having' in data (1): ngedi 'see' in data (2), with two core arguments, they are ‘ana no’ ‘his son’ 'and due do 'two people' in data (1), then, no ‘he’ and pidu bue motto ‘seven stars’ in data (2).. Whereas the intransitive sentence has no object. Then, the arrangement of functional elements is Subject + Predicate and Predicate + Subject. The following is an example of the intransitive sentence of Savu: (3) ta mari ina; (4) ro kako la rae; the intransitive sentence of Savu language indicates that they do not have objects. In data (3) ta mari 'laugh’ is the verb; ina ‘lady' is the subject. As well as in data (4) ro 'they’ is the subject, while kako la ‘go to' and rae ‘adverb of place’.